Wenxin Granules Influence the TGFβ-P38/JNK MAPK Signaling Pathway and Attenuate the Collagen Deposition in the Left Ventricle of Myocardial Infarction Rats - Ya Huang; Aiming Wu; Lixia Lou; Dongmei Zhang; Bo Nie; Yizhou Zhao; Keke Liu; Mingjing Zhao; Hongcai Shang (Cardiology Research and Practice)
Background. A large number of proinflammatory/anti-inflammatory cytokines are produced in the extracellular matrix (ECM) after myocardial infarction (MI), and the inflammatory pathways activated by these inflammatory stimuli are involved in the regulation of lesions with excessive accumulation of ECM. Wenxin granules can play a protective role against MI, but the mechanism of its effect on the inflammatory pathway and ECM collagen expression is still unclear. Objective. To verify the effect of Wenxin granules on the inflammatory pathway and collagen expression after MI. Method. The proximal left anterior descending coronary artery in rats was ligated to induce acute MI. Then, animals were randomly assigned to the model group, the Carvedilol group, and the Wenxin Granules group. In addition, sham operation rats were used as the control group. 10 rats were allocated in each group. Gavage was given once a day for 4 weeks. The changes of cardiac hemodynamics were detected by the catheter method, morphological changes were observed by HE staining, and myocardial tissue collagen volume was counted by Immunohistochemistry combined with Masson staining, and the expression of inflammatory TGFβ-p38/JNK MAPK signal pathway markers was detected by Western blot. Results. Wenxin granules could significantly improve the hemodynamics, so that the fibrosis scar was relatively dense and uniform, and the residual myocardium was relatively neat, while Collagen type I and III volume and TGFβ expression levels were lessened. Although there were no differences in the expression of CTGF, p38, and JNK proteins, their phosphorylation levels showed significant differences. Conclusion. Wenxin granules can affect the inflammation-related TGFβ-p38/JNK MAPK signaling pathway and change the structural properties of myocardium and scar after MI by attenuated collagen deposition in the left ventricular myocardial tissue to improve cardiac function.